2017
DOI: 10.3390/ijerph14070712
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset of Type 1 Diabetes and Educational Field at Upper Secondary and University Level: Is Own Experience an Asset for a Health Care Career?

Abstract: Ill health in early life has a significant negative impact on school grades, grade repetition, educational level, and labor market outcomes. However, less is known about qualitative socio-economic consequences of a health shock in childhood or adolescence. We investigate the relationship between onset of type 1 diabetes up to age 15 and the probability of choosing and completing a health-oriented path at upper secondary and university level of education. We analyze the Swedish Childhood Diabetes Register, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Other studies have further discovered that individuals who decide to pursue a career in health care were more likely to have firsthand experience with a childhood-onset disease (Lovén & Carlsson, 2017;Szilagy et al, 2019). This was exemplified in the current study, where participants all had a childhood-onset condition and detailed their interest to continue working in the healthcare environment.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Other studies have further discovered that individuals who decide to pursue a career in health care were more likely to have firsthand experience with a childhood-onset disease (Lovén & Carlsson, 2017;Szilagy et al, 2019). This was exemplified in the current study, where participants all had a childhood-onset condition and detailed their interest to continue working in the healthcare environment.…”
Section: Discussionmentioning
confidence: 55%
“…A previous experience with healthcare may contribute to an individual's decision to pursue a career in healthcare. Individuals with a childhood-onset disease or condition were more likely to choose a health-related course of study or career (Lovén & Carlsson, 2017;Szilagy et al, 2019). Lovén and Carlsson (2017) reported that participants who had an early onset of type 1 diabetes gravitated toward health careers.…”
Section: Past Health Care Experiencesmentioning
confidence: 99%
See 1 more Smart Citation